1984
DOI: 10.1002/jsfa.2740350207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary‐induced changes in milk urea levels on the heat stability of milk

Abstract: Two experiments were carried out to investigate the relationship between milk urea content and the heat stability of the protein in the skim milk. In experiment 1, four cows were offered a diet of grass silage with different amounts of hay and a protein concentrate. Although there were individual differences between the cows in the relationship between coagulation time and milk pH, there was a significant correlation between milk urea content and the maximum coagulation time. In experiment 2, two groups of fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hence, regression analysis of the entire data set for all milks showed that HCT at natural pH and HCT max correlated negatively with lactose content and lactose-to-protein ratio (P < 0.01) and positively with urea content (P < 0.05; Table 5). Other studies have also observed a positive correlation between the HCT max and urea concentration of seasonal milks with 25 to 55 mg urea/100 mL (Holt et al, 1978;Kelly et al, 1982), and individual cow milks with 35 to 60 mg urea/100 mL (Banks et al, 1984). Lactose undergoes thermal-induced degradation to organic acids (e.g., formic) upon heating at temperatures of 140°C, and thereby it reduces the pH of the milk during the HCT assay.…”
Section: Processing Characteristics Of Rsmmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, regression analysis of the entire data set for all milks showed that HCT at natural pH and HCT max correlated negatively with lactose content and lactose-to-protein ratio (P < 0.01) and positively with urea content (P < 0.05; Table 5). Other studies have also observed a positive correlation between the HCT max and urea concentration of seasonal milks with 25 to 55 mg urea/100 mL (Holt et al, 1978;Kelly et al, 1982), and individual cow milks with 35 to 60 mg urea/100 mL (Banks et al, 1984). Lactose undergoes thermal-induced degradation to organic acids (e.g., formic) upon heating at temperatures of 140°C, and thereby it reduces the pH of the milk during the HCT assay.…”
Section: Processing Characteristics Of Rsmmentioning
confidence: 91%
“…Such variations influence the processing behavior of RSM owing to their effects on buffering capacity, degree of heat-induced acidity, or susceptibility of protein to aggregation (Pouliot and Boulet, 1991;Rattray and Jelen, 1996;Sikand et al, 2010). Much information is available on the effects of season and cow diet on the processing characteristics of milk, such as rennet coagulability (O'Brien et al, 1999;Guinee et al, 2001), heat stability (Holt et al, 1978;Kelly, 1982;Banks et al, 1984), and ethanol stability (ES;O'Brien et al, 1997;Horne et al, 1986;Chen et al, 2014). In contrast, fewer studies have investigated seasonal changes in the composition of SMP or its functionality or processing behavior upon reconstitution to RSM.…”
Section: Introductionmentioning
confidence: 99%
“…Palrmtic and oleic acids are the major fatty acids affecting the melting point. Tables 4 and 5 show that total C,,fatty acids recorded the highest vaIues in groups B and C. Because of the relatively specific action of stearoyl coA desaturase, increasing the content of C fatty acids will increase that of oleic acid and decrease the de novo synthesis of palmitic acid (Banks et al 1984). ' .…”
Section: Resultsmentioning
confidence: 97%
“…The addition to or removal of urea from milk causes marked changes in heat stability (Muir and Sweetsur, 1977). There is a highly significant statistical correlation between seasonally observed variations in heat stability and urea contents (Kelly et al, 1982;Banks et al, 1984). The effect of heat on urea could be of importance for protein stability.…”
Section: Introductionmentioning
confidence: 99%